PENGETAHUAN MENDAUR ULANG SAMPAH RUMAH TANGGA DAN NIAT MENDAUR ULANG SAMPAH - I Made Bayu Dirgantara (Faculty of Economics and Business Diponegoro University, 2013)
Waste segregation done at the production point to ensure higher material recycling, one frequently use attemp to ensure the effort is by encouraging waste segregation at household level. In fact household participation in recycling is low therefore the research on factor that encourage household involvement on their waste segregation or waste recycling is arrouse. Oskamp et al. (1991) stated that specific recycling knowledge is more related to recycling intention compare to general environmental knowledge issues. This research will analyze causal relationship between waste recycling knowledge with waste segregation intention. Method apply is experimental method. Result with t-test shows that experiment done succesfully. T-test shows difference intention to segregate waste befor and after treatment applied. Household waste recycling knowledge on participant shaped from information absorb by individuals through stimulus prepared so that individuals understand completelly the benefit of household waste recycling and encorage individual household waste recycling intention. Keywords :Waste recycling knowledge, Waste segregation intention, Household participation.